Penguatan Karakter di Era Literasi Digital melalui Multiliteracy Integrative Learning Model - Vivi Indriyani; Delsy Arma Putri; Rizka Dwi Rahmayani; Justitiayu Novelly (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: Character building is a crucial aspect of 21st-century education, particularly in the digital era, as students are frequently exposed to various digital content. However, its implementation still faces various challenges in the school environment, particularly in learning contexts that do not fully support the internalization of character values. This study aims to examine the effectiveness of the Multiliteracy Integrative Learning Model in strengthening students' character formation, particularly in terms of honesty, discipline, and responsibility. This study used a descriptive quantitative approach with observation sheets as the main instrument. The research subjects consisted of students from two high schools selected purposively. Data were analyzed using descriptive statistics with average calculations to interpret students' character tendencies. The results showed that students' character values were formed through teacher guidance interactions and habituation in the learning environment. In general, students showed a positive tendency in developing honesty, discipline, and responsibility, although more systematic and continuous reinforcement is needed in the learning process.Abstrak: Penguatan karakter merupakan aspek krusial dalam pendidikan abad ke-21, khususnya di era digital, karena pada era ini siswa kerap terpapar berbagai konten digital. Namun, penerapannya masih menghadapi berbagai tantangan di lingkungan sekolah, terutama dalam konteks pembelajaran yang belum sepenuhnya mendukung internalisasi nilai-nilai karakter. Penelitian ini bertujuan untuk mengkaji efektivitas Multiliteracy Integrative Learning Model dalam memperkuat pembentukan karakter siswa, khususnya dalam hal kejujuran, disiplin, dan tanggung jawab.. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan lembar observasi sebagai instrumen utama. Subjek penelitian terdiri atas siswa dari dua sekolah menengah atas yang dipilih secara purposive. Data dianalisis menggunakan statistik deskriptif dengan perhitungan rata-rata untuk menginterpretasi kecenderungan karakter siswa. Hasil penelitian menunjukkan bahwa nilai karakter siswa terbentuk melalui interaksi bimbingan guru, dan pembiasaan dalam lingkungan pembelajaran. Secara umum, siswa menunjukkan kecenderungan positif dalam mengembangkan sikap jujur, disiplin, dan bertanggung jawab, meskipun diperlukan penguatan yang lebih sistematis dan berkelanjutan dalam proses pembelajaran.